Smart e-laundry monitoring system by using IoT - Muhammad Emir Husaini, Mohamad Nor; Mohd Faizal, Ab Razak; Ahmad Firdaus, Zainal Abidin (2021)
Nowadays people tend to do laundry outside of their house due to the limitation of time, space and machine such as a dryer. Therefore, doing laundry already become a weekly routine for certain families to ensure their clothes are clean and fresh. Hence, we can’t deny that the washing machine has a great impact on our society as it has a lot of advantages that able to help people to make their life more efficient. But, there is some improvement that we can make to every washing machine especially to the company that provides self-service laundry as their business to ensure everything is run smoothly.